Instytucja - Gasparski, Wojciech (The Institution, 2006)
The paper examines the concept of institution. First the sociological understanding of the concept is reviewed, then the institutional economics’ understanding of the concept is characterized. In the second part an organization as an institution and its axiological context are discussed. Part three is devoted to the concept of social role institutionalized by collection of values attached to the role. Finally theses extracted from Professor Bożena Klimczak works are presented as the summa of its kind to give her position of the institution par excellence.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1131, s. 13-24